Proteins in stool as biomarkers for non‐invasive detection of colorectal adenomas with high risk of progression. Issue 3 (13th January 2020) - Komor, Malgorzata A; Bosch, Linda JW; Coupé, Veerle MH; Rausch, Christian; Pham, Thang V; Piersma, Sander R; Mongera, Sandra; Mulder, Chris JJ; Dekker, Evelien; Kuipers, Ernst J; van de Wiel, Mark A; Carvalho, Beatriz; et al.
Abstract: Screening to detect colorectal cancer (CRC) in an early or premalignant state is an effective method to reduce CRC mortality rates. Current stool‐based screening tests, e.g. fecal immunochemical test (FIT), have a suboptimal sensitivity for colorectal adenomas and difficulty distinguishing adenomas at high risk of progressing to cancer from those at lower risk. We aimed to identify stool protein biomarker panels that can be used for the early detection of high‐risk adenomas and CRC. Proteomics data (LC–MS/MS) were collected on stool samples from adenoma ( n  = 71) and CRC patients ( n  = 81) as well as controls ( n  = 129). Colorectal adenoma tissue samples were characterized by low‐coverage whole‐genome sequencing to determine their risk of progression based on specific DNA copy number changes. Proteomics data were used for logistic regression modeling to establish protein biomarker panels. In total, 15 of the adenomas (15.8%) were defined as high risk of progressing to cancer. A protein panel, consisting of haptoglobin (Hp), LAMP1, SYNE2, and ANXA6, was identified for the detection of high‐risk adenomas (sensitivity of 53% at specificity of 95%). Two panels, one consisting of Hp and LRG1 and one of Hp, LRG1, RBP4, and FN1, were identified for high‐risk adenomas and CRCs detection (sensitivity of 66% and 62%, respectively, at specificity of 95%). Validation of Hp as a biomarker for high‐risk adenomas and CRCs was performed using an antibody‐based assay in FIT samples from a subset of individuals from the discovery series ( n  = 158) and an independent validation series ( n  = 795). Hp protein was significantly more abundant in high‐risk adenoma FIT samples compared to controls in the discovery ( p  = 0.036) and the validation series ( p  = 9e‐5). We conclude that Hp, LAMP1, SYNE2, LRG1, RBP4, FN1, and ANXA6 may be of value as stool biomarkers for early detection of high‐risk adenomas and CRCs. © 2019 Authors. Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.